Karnaugh Maps Adaptability to Implement Multiple-Actuator Pneumatic Circuits - Nather, ALZahraa; Salloom, Maher Yahya; Azizi, Amir; Siallagan, Sahala (Al-Khwarizmi Engineering Journal, 2024)
The pneumatic circuits have the benefit of having a low energy consumption and not polluting the air. Therefore, pneumatic installations are utilized in a variety of technological disciplines. The demands of industrial dynamics call for quick responses and minimal setup periods. Pneumatic equipment has to be adaptable and undergo ongoing production cycle changes to meet customer demands for flexibility. quick responses and minimal setup periods. Pneumatic equipment must be adaptable and undergo ongoing production cycle changes to meet customer demands for flexibility. This approach is often accomplished by completely rebuilding the system. The control system is part of it. It is easier to adjust to the new job cycle when the control system is included. By using the Karnaugh mapping technique, these problems can be solved. The technique enables circuit control with a (PLC). This study’s goal is to minimize startup times by identifying the collection of ideal logical equations. Any pneumatic circuit may be electrically or pneumatically controlled according to the equation. This approach ease creates the process of creating sequence control scheme, whether the scheme uses electro-pneumatic systems or pure pneumatic control. This approach may guarantee both the intended sequential cycle and the least amount of command variables needed to run the control circuit. This research demonstrates how to build a pneumatic control system for the coiling machine’s six cylinders using Karnaugh Maps. The logical equations are generated in a simplified form using the stated principles, and they are easy to use both pneumatically and electro-pneumatically. To implement the technique, pneumatic/electro-pneumatic circuit simulation software is used (Automation Studio and Fluid Sim). Also, the technique includes Ladder Diagram Language transformation.